Development board based on the TMS320F28335 DSP for applications of power electronics - Saavedra, Julian; Firacaitve, Jonathan; Trujillo, Cesar (TECCIENCIA, 2015)
This paper presents the design of a special purpose development board for power applications based on the digital signal processor (DSP) TMS320F28335. We also propose some considerations for the design of any four-layer printed circuit line with international recommendations to counteract the EMI (electromagnetic interference) and increase the EMC (electromagnetic compatibility). Additionally, the main features of each module on the board and their respective conditioning circuits designed are presented in order for the development board to be useful for any application of power electronics as motor control, switching power supplies, LED lighting, communications through the electric network, etc. Finally, a test protocol to verify the performance of the card and the comparison between the final cost per unit and similar cards on the market were performed.